Acute kidney injury following endovascular intervention for peripheral artery disease. Issue 2 (15th January 2021) - Katsogridakis, E; Lea, T; Yap, T; Batchelder, A; Saha, P; Diamantopoulos, A; Saratzis, N; Davies, R; Zayed, H; Bown, M J; Saratzis, A
Abstract: Background: The incidence of, and risk factors for, acute kidney injury (AKI) after endovascular intervention for peripheral artery disease (PAD) remain unknown. The aim of this study was to assess the proportion of patients who develop AKI and explore the risk factors. Methods: Prospectively collected data on patients undergoing femoropopliteal endovascular intervention for symptomatic PAD across three vascular centres were analysed. The proportion of patients developing AKI (according to the Kidney Disease Improving Global Outcomes definition) within 48 h, and the proportion developing the composite Major Adverse Kidney Events (MAKE) endpoints (death, dialysis, drop in estimated glomerular filtration rate at least 25 per cent) at 30 days (MAKE30) and remains 90 days (MAKE90) were calculated. Multivariable regression analysis was used to assess predictors of AKI, and the association between AKI and death. Results: Some 2041 patients were included in the analysis. AKI developed in 239 patients (11.7 per cent), with 47 (2.3 per cent) requiring dialysis within 30 days, and 18 (0.9 per cent) requiring ongoing dialysis. The MAKE30 and MAKE90 composite endpoints were reached in 358 (17.5 per cent) and 449 (22.0 per cent) patients respectively. Risk factors for AKI were age, sex, congestive heart failure, chronic limb-threatening ischaemia, emergency procedure, and pre-existing chronic kidney disease. AKI, dementia, congestive heart failure, and major amputation were risk factors for medium-term mortality. Conclusion: AKI is a common complication after intervention for PAD and is associated with medium-term mortality. Abstract : Acute kidney injury (AKI) is a common problem after peripheral endovascular intervention. However, its exact prevalence remains unclear. This large multicentre study examined the prevalence of, and risk factors for, AKI in patients treated for symptomatic peripheral artery disease. DES, drug-eluting stent; DCB, drug-coated balloon; PBA, plain balloon angioplasty. AKI common and associated with medium-term mortality.